The World's Oldest Church - Peppard, Michael (New Haven Yale University Press, 2016)
Michael Peppard provides a historical and theological reassessment of the oldest Christian building ever discovered, the third-century house-church at Dura-Europos. Contrary to commonly held assumptions about Christian initiation, Peppard contends that rituals here did not primarily embody notions of death and resurrection. Rather, he portrays the motifs of the church$1 (Bs wall paintings as those of empowerment, healing, marriage, and incarnation, while boldly reidentifying the figure of a woman formerly believed to be a repentant sinner as the Virgin Mary. This richly illustrated volume is a breakthrough work that enhances our understanding of early Christianity at the nexus of Bible, art, and ritual.s
English
Keywords: Ancient history: to c 500 CE; History; Annunciation; Anointing; Baptism; Baptistery; Dura-Europos; Jesus; Psalms